1979
DOI: 10.1002/ijc.2910230504
|View full text |Cite
|
Sign up to set email alerts
|

Low natural killer‐cell activity and immunoglobulin levels associated with smoking in human subjects

Abstract: Previous studies have shown that smoking i s associated with a high incidence of certain malignancies and a high incidence of metastatic spread of melanoma. The purpose of the present study was t o examine whether this high incidence of malignancy could be associated with certain aspects of immune function believed to be important in restricting tumour growth. Age-and sex-matched smoking and non-smoking normal subjects and male, smoking and non-smoking melanoma patients, were studied for the natural killing (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
119
1
3

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(128 citation statements)
references
References 26 publications
5
119
1
3
Order By: Relevance
“…Thus amalgam burden was not related to any sign of immunologic disturbance. Smoking has been shown to influence serum immunoglobulin levels (37) and also the activity of natural killer cells (38). A negative correlation between the in vitro 412 production of TNFa and IL-I and smoking, as seen in our study, has not been reported earlier.…”
Section: Discussionsupporting
confidence: 58%
“…Thus amalgam burden was not related to any sign of immunologic disturbance. Smoking has been shown to influence serum immunoglobulin levels (37) and also the activity of natural killer cells (38). A negative correlation between the in vitro 412 production of TNFa and IL-I and smoking, as seen in our study, has not been reported earlier.…”
Section: Discussionsupporting
confidence: 58%
“…Animal experiments have shown that lower NK cell activity is associated with higher cancer incidence, while studies on NK cell activity on humans have found significantly lower NK activity among smokers compared to non-smokers (Ferson et al 1979;Ginns et al 1985;Phillips et al 1985;Talmadge et al 1980). Another study found that smoking decreased both the quantity and function of NK cells, and the quantity and function remained impaired after smoking cessation, while other white blood cell functions returned to normal (Tollerud et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of NK cell activity in humans is complicated by the fact that many patients use tobacco and other drugs that are known to affect NK cell activity (36,37). Furthermore, alcoholics are frequently malnourished (38).…”
Section: Discussionmentioning
confidence: 99%